The chromosome 6p22 haplotype associated with dyslexia reduces the expression of KIAA0319, a novel gene involved in neuronal migration. - Paracchini, S; Thomas, A; Castro, S; Lai, C; Paramasivam, M; Wang, Y; Keating, B; Taylor, J; Hacking, D; Scerri, T; Francks, C; Richardson, A; et al. (2006)
Dyslexia is one of the most prevalent childhood cognitive disorders, affecting approximately 5% of school-age children. We have recently identified a risk haplotype associated with dyslexia on chromosome 6p22.2 which spans the TTRAP gene and portions of THEM2 and KIAA0319. Here we show that in the presence of the risk haplotype, the expression of the KIAA0319 gene is reduced but the expression of the other two genes remains unaffected. Using in situ hybridization, we detect a very distinct expression pattern of the KIAA0319 gene in the developing cerebral neocortex of mouse and human fetuses. Moreover, interference with rat Kiaa0319 expression in utero leads to impaired neuronal migration in the developing cerebral neocortex. These data suggest a direct link between a specific genetic background and a biological mechanism leading to the development of dyslexia: the risk haplotype on chromosome 6p22.2 down-regulates the KIAA0319 gene which is required for neuronal migration during the formation of the cerebral neocortex.